Two Alkaloids From Delphinium brunonianum Royle, Their Anti-inflammatory and Anti-oxidative Stress Activity via NF-κB Signaling Pathway - Tang, Qi; Chen, Sitan; Rizvi, Syed Arif Hussain; Qu, Jiaojiao; Wang, Li; Wang, Senye; Ma, Changyang; Liu, Lijun; Kang, Wenyi (Frontiers in Nutrition, 2022)
In this study, we isolated and identified four compounds in Delphinium brunonianum Royle, and they were Delbrunine (1), 4-O-α-D-Glucosyl benzoic acid (2), Kaempferol 3-O-β-D-glucopyranoside 7-O-α-L-rhamnopyranoside (3) and Eldeline (4). Furthermore, the anti-inflammatory activity of these compounds was screened in RAW264.7 cells. The results showed that the anti-inflammatory activities of compounds 2 and 3 were weak, and 1, 4 had good anti-inflammatory activity. The macrophage inflammation model was established by lipopolysaccharide (LPS). Then, the anti-inflammatory activity was evaluated by ELISA kits, qRT-PCR experiment and western blot experiment. And the anti-oxidative stress activity was assessed by flow cytometry. The results showed that compounds 1, 4 could significantly inhibit the elevation of inflammatory factors nitric oxide (NO), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and also had obvious inhibitory effects on the production of inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX-2). In addition, compounds 1 and 4 could effectively inhibit the overexpression of reactive oxygen species (ROS) in RAW264.7 cells that activated by LPS. These results indicated that compounds 1 and 4 may exert anti-inflammatory and anti-oxidative stress effects through the NF-κB signaling pathway.